Effects of emotional intelligence training and self-efficacy technique on pre-retirement anxiety of public servants in Ibadan, Nigeria. (2000)
Retirement is voluntary or involuntary withdrawal from active work role. It poses emotional problem to several people who are about to retire and even those who are still having many years to spend in service. Pre-retirement anxiety could, therefore, constitute psychological problems which, more often than not, brings about apprehension, maladjustment and social tensions. Past studies on retirement focused on mental health and influence of sociological factors, only few studies are available on pre-retirement anxiety. This study, therefore, investigated effects of Emotional Intelligence Training (EIT) and Self-efficacy Technique (SET) on pre-retirement anxiety of public servants in Ibadan, Nigeria. A pre-test, post-test, control group quasi-experimental design with a 3x2x2 factorial matrix was used for the study. There were two treatment conditions (EIT and SET) and a control group. The moderator variables were gender and self-esteem. Multistage and stratified sampling techniques were used to select 103 Oyo State public servants (54 males and 49 females) who participated in the study. The participants were randomly assigned into the experimental and control groups. Sarason’s General Anxiety Scale (=0.81) and Rosenberg Self-esteem Scale (=0.77) were employed to collect data. The experimental groups were exposed to eight weeks training sessions, while participants in the control group received no training. Nine hypotheses were tested at 0.05 level of significance. Data were analysed using Analysis of Covariance. There was significant difference in the anxiety of pre-retirees exposed to treatment and control groups (F (2, 97) =38.77; P<0.05). The participants exposed to EIT performed better ( =19.26) than those exposed to SET ( =23.09) on the measure of pre-retirement anxiety. The participants in the EIT performed better ( = 19.26) than those in the control ( = 28.47) on the level of pre-retirement anxiety. Treated participants in SET were also better ( = 23.09) than those in the control ( = 28.47). However, there was no significant difference in the anxiety of pre-retirees males and females exposed to EIT and those exposed to SET. Similarly, no significant difference was found in the anxiety of pre-retirees with low and high self-esteem exposed to EIT and those exposed to SET. In the same vein, no significant difference was found in the interaction effect of treatment and gender on the anxiety of intending retirees. Emotional intelligence training and self-efficacy techniques were effective in reducing pre-retirement anxiety of public servants. Counselling and social psychologists should, therefore, utilise the two strategies in the management of pre-retirement anxiety of public servants. These strategies should also be incorporated into the retirement policy of state and federal governments.